Une Citoyenneté sans Cité, des cités sans citoyenneté: Државјанство без Држава, предградија без право на граѓанство - Štiks, Igor; Angelovska, Despina (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Igor Štiks | Игор Штикс Title (French): Une Citoyenneté sans Cité, des cités sans citoyenneté Title (Macedonian): Државјанство без Држава, предградија без право на граѓанство Translated by (French to Macedonian): Despina Angelovska | Деспина Ангеловска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 113-148 Page Count: 35 Citation (French): Igor Štiks, “Une Citoyenneté sans Cité, des cités sans citoyenneté,” Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006): 113-148. Citation (Macedonian): Игор Штикс, „Државјанство без Држава, предградија без право на граѓанство“, превод од француски Деспина Ангеловска, Идентитети: списание за политика, род и култура, т. 5, бр. 1 (зима 2006): 113-148.